Effects of No-Till Seeding and Fertilization on Vegetation Restoration and Soil Physicochemical Properties in Alpine Degraded Grazing Grasslands - Xiaojing Hu; Qunce Sun; Shuzhen Zhang; Weisi Li; Xuerui Wang; Runzhou Long; Guili Jin; Bo Zhang (Agronomy)
This study evaluated the effects of no-till seeding and fertilization on the restoration of degraded grazing grasslands in Bayinbuluke. Poaceae species were selected for no-till replanting, with Elymus dahuricus, Puccinellia distans, and Festuca ovina mixed in a 2:1:1 ratio. Four sowing rates were applied: 0 g/m2 (A0), 2 g/m2 (A1), 4 g/m2 (A2), and 6 g/m2 (A3). Diammonium phosphate (N 18%, P2O5 46%) was used as fertilizer, with four fertilization rates: 0 g/m2 (B0), 7.5 g/m2 (B1), 15 g/m2 (B2), and 22.5 g/m2 (B3). A total of 16 treatments were applied. The study assessed the changes in grassland productivity, species diversity, and soil physicochemical properties. The results showed that no-till replanting significantly increased the aboveground biomass by 81%, species richness by 55.8%, and the Shannon–Wiener diversity index by 64.2%. Fertilization significantly increased productivity, with dry hay yield rising by 60.9% to 81%. When 22.5 g/m2 of fertilizer was applied, the contents of total phosphorus, total nitrogen, available phosphorus, and organic matter in the soil increased by 43.4%, 50.6%, 66%, and 31.2%, respectively. Fertilization also improved the stability of soil aggregates, with the proportion of large aggregates increasing by 18.2%. The findings suggest that no-till seeding and fertilization significantly promote grassland restoration, with soil moisture and nutrient availability being key drivers of vegetation growth and community diversity.